Cooperation and Communication: Benefits for Non-Industrial Private Forest Landowners - Nicole Ricci; Chris Demers; Alan Long (EDIS, 2010)
FOR235, a 6-page fact sheet by Nicole Ricci, Chris Demers. and Alan Long, discusses various opportunities available to landowners needing resources for successful long-term land management. Includes references. Published by the UF School of Forest Resources and Conservation, March 2010.